2017
DOI: 10.4212/cjhp.v70i1.1626
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination for Secondary Prevention of Cardiovascular Events: A Systematic Review

Abstract: RÉSUMÉContexte : La grippe est une infection courante des voies respiratoires qui peut causer des complications, notamment des événements cardiovasculaires. On a montré que la grippe double les risques d'infarctus du myocarde. De plus, les patients atteints d'une maladie cardiovasculaire sont les plus menacés. La vaccination contre la grippe a été associée à une réduction des cas d'infarctus du myocarde, de maladie cérébrovasculaire et de décès.Objectif : Évaluer les données probantes montrant que la vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Several ecologic and molecular studies found that patients with coronary artery disease are vulnerable and at risk of respiratory infections [ 1 , 2 , 3 , 4 ]. Then, randomized clinical trials, retrospective studies, and metanalyses have shown that immunization reduces mortality and morbidity among them [ 11 , 12 , 13 , 47 , 48 , 49 , 50 ]. However, in this cohort, known CAD was not associated with increased rates of immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ecologic and molecular studies found that patients with coronary artery disease are vulnerable and at risk of respiratory infections [ 1 , 2 , 3 , 4 ]. Then, randomized clinical trials, retrospective studies, and metanalyses have shown that immunization reduces mortality and morbidity among them [ 11 , 12 , 13 , 47 , 48 , 49 , 50 ]. However, in this cohort, known CAD was not associated with increased rates of immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The body of evidence confirms that Influenza vaccination (IV) and Pneumococcal vaccination (PV) are related to a decrease in the rate of different CV outcomes, such as myocardial infarction (MI), heart failure (HF) hospitalization, and CV mortality [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, some barriers were identified for implementing these prevention strategies, which are grouped in patient’s decision (vaccine hesitancy, prior experience, fake news), health care providers knowledge and attitude towards vaccination, and health care system barriers, that lead to a lower than expected immunization rate in Latin America and globally [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Influenza vaccination has been recommended as the primary prevention method for influenza infection in >65-year-olds since the 1960s, [102][103][104][105] and not only prevents influenza infection but plays a key role in prevention of secondary events and complications, including cardiovascular morbidity and mortality. 106,107 Vaccination of healthcare professionals (HCPs) may also be important in protecting elderly patients from viral infections and complications and has been a consideration during the COVID-19 pandemic. However, the true impact on both influenza and SARS-CoV-2-related infection is yet to be demonstrated conclusively.…”
Section: Influenza Vaccinationmentioning
confidence: 99%
“…Pooled data from small randomized controlled trials show a relative reduction of 50% in cardiovascular deaths and 43% in cardiovascular events, with 54% protection for patients who have an acute coronary syndrome within 12 months [15]. However, small sample sizes of the available RCTs, as well as variable study outcomes reported in these studies are a limitation.…”
Section: Cvd and Influenza Vaccinementioning
confidence: 85%